PENGARUH KEMAMPUAN PEDAGOGIK TUTOR TERHADAP PENGEMBANGAN SDM WARGA BELAJAR DI PKBM AL-IKHRAM - Ayu Wulandari Siregar; Teovilla Grace Natasia Br Ginting; Apryanti Situmorang; Tari Patunnisa; Sonya Letare Nababan; Miranda Afriza; Silvia Mariah; Sitti Subaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of tutors' pedagogical abilities on the development of human resources (HR) of students at PKBM Al-Ikhram. This study uses a quantitative approach with a simple linear regression analysis method. The population in this study amounted to 315 students, with a sample of 30 people selected based on their active participation in learning. Data collection techniques were carried out through questionnaires, observation, and documentation. The results showed that tutors' pedagogical abilities have a significant influence on the development of human resources of students, with a significance value of 0.000 (p < 0.05). The correlation coefficient (R) of 0.930 indicates a very strong relationship, while the coefficient of determination (R²) of 0.865 indicates that tutors' pedagogical abilities contribute 86.5% to the development of human resources of students. These findings indicate that the better the tutors' pedagogical abilities in planning, implementing, and evaluating learning, the higher the development of human resources of students. Therefore, improving tutors' pedagogical competence is an important factor in improving the quality of learning in non-formal education.